Pengaruh Isometric Handgrip Training terhadap Tekanan Darah pada Lansia dengan Hipertensi di Wilayah Kerja UPTD Puskesmas Jatirahayu - Farouq Muhammad Insaan Kamal; Mohammad Ali; Liza Laela Abida (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Hypertension is a common health problem among the elderly and increases the risk of stroke, heart failure, and kidney failure. Isometric Handgrip Training (IHT) is a simple and practical non-pharmacological intervention that may help reduce blood pressure; however, its effectiveness still needs further investigation. Jatirahayu Public Health Center is one of the health centers with a relatively high number of hypertension cases, reaching 252 cases. Objectives: To determine the effect of Isometric Handgrip Training on blood pressure among elderly patients with hypertension. Methods: This study employed a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 20 respondents divided into an intervention group (n=10) and a control group (n=10) selected using purposive sampling. The intervention group received IHT exercises three times per week for four weeks, while the control group only received health education through leaflets. Blood pressure was measured using a digital sphygmomanometer. Results: The paired sample t-test showed a significant reduction in systolic blood pressure in the intervention group with a mean difference of −10.40 mmHg (p=0.004) compared to −1.50 mmHg in the control group, as well as a reduction in diastolic blood pressure with a mean difference of −6.80 mmHg (p=0.016) compared to −0.80 mmHg in the control group. The independent sample t-test showed a significant difference between the intervention and control groups in systolic blood pressure (p=0.008), but not in diastolic blood pressure (p=0.051). Conclusion: Isometric Handgrip Training was effective in reducing systolic blood pressure among elderly patients with hypertension, but it did not show a significant effect on diastolic blood pressure after four weeks of intervention. Keywords: Hypertension, Elderly, Isometric Handgrip Training, Blood Pressure.